(untitled) - Spears, Richard A. (Lincolnwood, Ill., USA, 1990)
Containing approximately 1400 words and phrases that should not be used by educated speakers of English, this dictionary of offensive and often inflammatory vocabulary is designed to inform rather than to offend or entertain. --This text refers to an out of print or unavailable edition of this title.
Keywords: English language,English language,Americanisms,Invective,Sex,Ngôn ngữ tiếng Anh,Ngôn ngữ tiếng Anh,Đặc ngữ Mỹ,Châm biếm,Giới tính; Dictionaries,Obscene words,Dictionaries,Slang,Dictionaries,Dictionaries,Dictionaries,Từ điển,Tiếng lóng,Từ tục tĩu,Từ điển,Từ điển,Từ điểm,Từ điển; United States,United States,Hoa Kỳ,Hoa Kỳ